Pendidikan Sosial dalam Membentuk Kesadaran dan Perilaku Hidup Bersih pada Anak Indonesia - Revalina Putri Pratami; Gina Aufa Maulida (Journal of Educational Research and Learning Analytics, 2025)
This study examines the effectiveness of social education in fostering clean and healthy living behaviors (PHBS) among Indonesian children to achieve the Indonesia Emas 2045 vision. Utilizing a qualitative-descriptive approach with literature from Scopus and 2024-2025 national reports, it identifies health challenges like 19.8% stunting prevalence and 58% inadequate school sanitation. Analysis reveals that behavior modeling by teachers and parents constitutes a primary determinant with high statistical significance (p=0.019). Furthermore, physical infrastructure availability exerts a dominant influence on children's hygiene practice consistency. Integrating digital technology within the Kurikulum Merdeka and the 2024-2030 School Sanitation Roadmap significantly bolsters student self-efficacy. Ultimately, transforming behavior into a sustainable health culture necessitates cross-sector synergy and consistent exemplary education to mitigate infectious diseases. This strategic investment enhances Indonesia’s human resource quality to develop a superior, intelligent, and strong-charactered future generation to achieve those long-term national development goals very effectively and successfully within the established timeline.